L’enseignement du contrepoint et de la fugue au Conservatoire de Paris (1858-1905) - Anthony Bergerault (Transposition)
This article attempts to describe the pedagogic project about counterpoint and fugue, and considers it in its context. The used documents are mostly historical sources, especially archives from the Conservatoire. The reconstitution of the considered teachings will be done in three points. First of all, the institutional organisation will be studied to situate the learning of these subjects as a part of a global formation for young musicians, specially destined to future composers. In a second time, our attention will be concentrated on the treatises published by the teachers of the Conservatoire themselves, often used in the classes, as a witnesses of their teaching and their pedagogy. Finally, the analysis of fugues written by students for their exam will inform us about the concrete result of the studies in counterpoint and fugue during these years.